Lipid content and wastewater treatment potential of Chlorella vulgaris and Scenedesmus obliquus isolated from Uzuncayır Dam Lake - Can Şafak Seyhaneyıldız; Can Erkan; Yılmaz Kadir (Oceanological and Hydrobiological Studies)
Production of microalgae for biodiesel, one of the alternative renewable energy sources, is costly due to nutrient media. Industrial and domestic wastewater contains nitrogen, phosphorus and other nutrients that are the primary food source for algae. Releasing this environmentally harmful effluent into receiving bodies of water, such as the sea or a freshwater reservoir, without prior treatment causes serious problems. Combining microalgae cultivation with wastewater treatment is a promising strategy for improving wastewater and reducing the cost of nutrient media required for algae production. In this study, wastewater obtained from a wastewater treatment facility was diluted with clean water to 0.25%, 50%, and 75% concentrations, and Chlorella vulgaris and Scenedesmus obliquus were cultured in these nutrient media for 20 days. As a result, microalgae increased their biomass and lipid content, while consuming nitrite, nitrate, phosphate, and ammonium from the wastewater as nutrients.